2002
DOI: 10.1002/syn.10139
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine‐sensitized animals show a marked increase in dopamine D2 high receptors occupied by endogenous dopamine, even in the absence of acute challenges

Abstract: While a range of dopamine D(2)-related behaviors are exaggerated in amphetamine-sensitized animals, studies of the dopamine D(2) receptor have reported either no change or a decrease in dopamine D(2) receptor density--especially when measured using radioraclopride. We hypothesized that a decrease in D(2) receptors may actually be "apparent" and that these receptors may still be present, but are noncompetitively "occupied" by endogenous dopamine. Animals sensitized to amphetamine (and their saline controls) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 16 publications
6
62
1
Order By: Relevance
“…The in vitro studies include competition assays between antagonist radiotracers and agonist ligands in the presence of non-hydrolysable GTP analogs (GppNHp), the latter converting the receptor from its high-affinity state to its low-affinity state (De Lean et al, 1980;Seeman et al, 2002Seeman et al, , 2005b. This differs from the approach in humans which involves a direct study of the high-affinity states with an agonist radioligand.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro studies include competition assays between antagonist radiotracers and agonist ligands in the presence of non-hydrolysable GTP analogs (GppNHp), the latter converting the receptor from its high-affinity state to its low-affinity state (De Lean et al, 1980;Seeman et al, 2002Seeman et al, , 2005b. This differs from the approach in humans which involves a direct study of the high-affinity states with an agonist radioligand.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, considering the successful in vivo detection of high-and low-affinity dopamine D2 receptors by Ross and Jackson (1989) High receptors in vitro (Seeman et al, 2002(Seeman et al, , 2005a, the present coinjection method was used to determine whether such an elevation in D2…”
Section: C](-)n-propyl-norapomorphine Selectively Labels D2mentioning
confidence: 99%
“…High receptors are consistently between 10 and 20% of the D2 population (Seeman et al, 2005a(Seeman et al, ,b, 2006 High receptors, these receptors should become increased in vivo in the amphetamine-sensitized rat, as occurs in vitro (Seeman et al, 2002). Hence, a series of amphetamine-sensitized rats was prepared, and the data in Figure 4 illustrate that 10 lg/kg NPA displaced 2.36-fold more [ In order to compare the amphetamine-induced 2.36-fold increase in D2…”
mentioning
confidence: 99%
“…Although it has been reported that experimenter-administered amphetamine increases the number of D2 High receptors (Seeman et al, 2002, no studies have examined the effects of self-administered cocaine on D2 High receptors, which is more directly relevant to human imaging studies. Therefore, in the present study we asked whether cocaine self-administration experience increases the proportion of D2 High receptors in the dorsal striatum, which could account for the well-documented behavioral hypersensitivity to D2 agonists seen in animals with a history of exposure to cocaine.…”
Section: Introductionmentioning
confidence: 99%